The Effect Of Communication And Teamwork On Employee Performance At PT. Riau Eramedia Indonesia Pekanbaru - Hamdanisyah, Aulia; Zainal, Haznil; Haznil, Alief Feisal (STEBIS Bina Mandiri, 2025)
This study aims to test and analyze the influence of communication and teamwork on employee performance at PT Riau Eramedia Indonesia Pekanbaru. This study is a quantitative study. The population in this study were all employees of PT Riau Eramedia Indonesia Pekanbaru totaling 53 employees. The sampling technique used was the census method so that the number of samples was 53 respondents. The data collection technique in this study used a questionnaire. The data analysis technique in this study used quantitative descriptive analysis and used SPSS. The results of this study indicate that communication and teamwork partially and simultaneously have a positive and significant effect on employee performance at PT Riau Eramedia Indonesia Pekanbaru. The contribution of communication and teamwork to employee performance is 82% with the remaining 18% explained by other variables not discussed in this study.